Neuroendocrine Factors and Head and Neck Squamous Cell Carcinoma: An Affair to Remember. (8th May 2018) - Solomon, Iulia; Voiculescu, Vlad Mihai; Caruntu, Constantin; Lupu, Mihai; Popa, Alexandra; Ilie, Mihaela Adriana; Albulescu, Radu; Caruntu, Ana; Tanase, Cristiana; Constantin, Carolina; Neagu, Monica; Boda, Daniel
Abstract : Head and neck squamous cell carcinoma (HNSCC) is one of the most aggressive malignancies. Therefore, the major goal of cancer treatment is inhibition of tumor cell growth and of metastasis development. In order to choose the best management option for HNSCC patients, we need to identify reliable prognostic factors and to develop new molecular techniques in order to obtain a better understanding of therapy resistance. By acting as neurohormones, neurotransmitters, or neuromodulators, the neuroendocrine factors are able to signal the maintenance of physiological homeostasis or progression to malignant disease. Certain neuropeptides possess strong antitumor properties acting as tumor suppressors and immunomodulators, providing additional benefits for future potential therapeutic strategies. In light of the current understanding, cancer starts as a localized disease that can be effectively treated if discovered on proper time. Unfortunately, more than often cancer cells migrate to the surrounding tissues generating distant metastases, thus making the prognosis and survival in this stage much worse. As cellular migration is mandatory for tumor invasion and metastasis development, searching for alternate controllers of these processes, such as the neuroendocrine factors, it is an active tremendous task.